2014
DOI: 10.1121/1.4892794
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of greatest temporary hearing threshold shift in harbor porpoises (Phocoena phocoena) depends on the noise level

Abstract: Harbor porpoises may suffer hearing loss when they are exposed to high level sounds. After exposure for 60 min to a 6.5 kHz continuous tone at average received sound pressure levels (SPLav.re.) ranging from 118 to 154 dB re 1μPa, the temporary hearing threshold shifts (TTSs) of a harbor porpoise were quantified at the center frequency (6.5 kHz), at 0.5, 1.0, and 1.3 octaves above the center frequency (9.2, 13.0, and 16.0 kHz), and at a frequency assumed to be ecologically important for harbor porpoises (125 kH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…These studies demonstrate that generally, there is a trade-off between exposure duration and level: exposures of even very short duration can cause TTS if the sound's level is high enough, and exposures of long duration do not need to include high level sounds in order to cause TTS. More recent TTS studies in marine mammals show that the spectral content of sounds in relation to the hearing sensitivity of the species also influences the shift induced (e.g., Finneran and Schlundt, 2013;Kastelein et al, 2014b), and that the temporal pattern of fatiguing sounds affects the shift induced (Kastelein et al, 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…These studies demonstrate that generally, there is a trade-off between exposure duration and level: exposures of even very short duration can cause TTS if the sound's level is high enough, and exposures of long duration do not need to include high level sounds in order to cause TTS. More recent TTS studies in marine mammals show that the spectral content of sounds in relation to the hearing sensitivity of the species also influences the shift induced (e.g., Finneran and Schlundt, 2013;Kastelein et al, 2014b), and that the temporal pattern of fatiguing sounds affects the shift induced (Kastelein et al, 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…There is now a large body of research-based evidence showing that particular construction-related activities, such as pile driving (Brandt et al 2011), seismic surveys (Stone & Tasker 2006) and dredging (Pirotta et al 2013) have negative impacts on marine mammals. Depending on the animals' proximity to the activity, the type of activity, and the context in which the area is being used by the animals, these may range from behavioural responses, such as displacement (Teilmann & Carstensen 2012, Thompson et al 2013a) through to physiological impacts, including a temporary or permanent threshold shift in hearing (Kastak et al 2005, Lucke et al 2009, Kastelein et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Since high frequencies are encoded shortly after the entry to the cochlea, they are subject to impulse-related effects even though the peak in the spectrum of the signal is lower. Such effects were also observed in Kastelein et al (2014a), who reported TTS to occur at increasingly higher frequencies with increasing noise exposure. When received levels of an explosion impulse exceed the threshold for causing a permanent hearing loss to part of the harbour porpoise's hearing range, a wider range of hearing is also likely to be negatively affected.…”
Section: Implication Of Underwater Explosions For the North Sea Harbomentioning
confidence: 55%
“…Data from Kastelein et al (2012b) suggest there could be a higher TTS/PTS exposure difference. Kastelein et al (2014a) demonstrated a positive correlation between frequency and rate of TTS increase. This would result in a wider offset between TTS and PTS than assumed in the present study and, consequently, a higher PTS threshold, especially for the low-frequency range containing most of the propagated energy from an explosion.…”
Section: Uncertainty In Estimated Impactsmentioning
confidence: 86%
See 1 more Smart Citation